Caracterização das concepções sobre ciência e natureza da ciência (NDC) presentes em um livro didático de ciências para o ensino médio sob o enfoque CTS - Santos, Mayla Silva (2024)
The science often portrayed by textbooks and understood by students is that of scientists dedicating their lives to experimentation and theory formulation based on discoveries. This study investigates the relationship between the History of Science, the Nature of Science, and textbooks, focusing on how these interactions shape the scientific conceptions of Chemistry students. The research originated from the author's experience as a basic education teacher, where difficulties in students assimilating scientific content and the need for a more critical and contextualized approach to teaching were observed. The main objective was to analyze the conceptions of the Nature of Science present in Chemistry textbooks from the National Textbook Program used in high school, and how these conceptions influence the formation of students' scientific views. Specific objectives included evaluating the representations of science in textbooks, analyzing the epistemological approach of scientific content, and investigating the inclusion of sociocientific and historical aspects. The importance of the research lies in exploring conceptions about science and the Nature of Science and how they can contribute to improving the teaching of Science/Chemistry, fostering an education that produces critical and well-informed citizens. Immersing students in a scientific culture is crucial for understanding science as a social and historical product, rather than merely a set of information. The dissertation adopts a qualitative approach, using textual analysis of Chemistry textbooks. Data were collected on representations of science, epistemological approaches, and the inclusion of historical and sociocientific aspects, with analysis based on narratives constructed from key theorists used in the investigation. Results indicate that textbooks often present a limited view of the Nature of Science, frequently overlooking its historical and social context. The research highlights the need for a more integrated approach that considers science as a dynamic and interactive phenomenon, reflecting cultural and social changes. Discussions emphasize the importance of education that values critical and contextualized scientific knowledge. It concludes that integrating the history and the Nature of Science into Chemistry teaching is essential for forming critical and aware students. Recommendations include revising textbooks and promoting ongoing teacher training for a richer and more contextualized scientific education. The research also highlights the importance of preparing students to face contemporary challenges, fostering a scientific culture that enables them to make informed decisions in their everyday lives.